Effect of oral administration of GABA on thermoregulation in athletes during exercise in cold environments: A preliminary study - Wang, Hongli; Cheng, Lin; Han, Yanbai (Frontiers in Nutrition, 2022)
Background: γ-aminobutyric acid (GABA), a common ingredient in sports supplements and other health products, regulates body temperature in the preoptic area and anterior hypothalamus (PO/AH). To date, no study has examined the effect of GABA on thermoregulation during exercise in humans in a cold temperature environment (11 ± 0.3℃, 45% ± 2% relative humidity). Methods: We performed a randomized, double-blind study. Ten trained male athletes consumed either a drink (3ml/kg weight) containing GABA(1000 mg, trial G) or an equivalent amount of placebo drink (trial C) before exercise. They rested for 20 minutes and then cycled at 60% of maximum output power for 40 minutes, pedaling at 60 rpm, and recovered for 20 minutes. Core temperature (Tc), skin temperature (upper arm, chest, thigh, calf), and heart rate (HR)were monitored at rest (T0), exercise begins (T20), 20 minutes of exercise (T40), the exercise ends (T60), and at recovery (T80). Results: Compared to T0, Tc decreased significantly at T20 and increased significantly at T40,T60 and T80 (p < 0.01). From 35-80 minutes, the Tc was higher in trial G (peaked at 37.96 ± 0.25℃) than in trial C (37.89 ± 0.37℃), but it failed to reach significant difference (p > 0.05); Tsk continued to increase during exercise and was significantly higher than T0 at T40 (p < 0.05),T60 and T80 (p < 0.01). There was no significant difference in Tsk between the two trials (p > 0.05). Conclusion: Our findings provide initial evidence that oral administration of GABA does not affect thermoregulation and has no adverse effects on the body as an ergogenic exercise supplement during exercise in cold environments.